2019
DOI: 10.1093/europace/euz011
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of implantable cardioverter-defibrillators and resynchronization devices to improve patient outcomes: dead end or way ahead?

Abstract: Remote monitoring (RM) has become a new standard of care in the follow-up of patients with implantable pacemakers and defibrillators. While it has been consistently shown that RM enables earlier detection of clinically actionable events compared with traditional in-patient evaluation, this advantage did not translate into improved patient outcomes in clinical trials of RM except one study using daily multiparameter telemonitoring in heart failure (HF) patients. Therefore, this review, focusing on RM studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…However, in the last decade the new generation of ICD devices that supports wireless technology has enabled remote monitoring of the device [ 3 - 6 ]. Consequently, in order to improve clinical practice of ICD follow-ups and to provide earlier detection of clinical problems, a wider use of remote patient monitoring (RPM) has been recommended by scientific associations in both Europe [ 5 ] and the United States [ 7 ], and has become the new standard of care for patient follow-up [ 8 - 10 ]. When a patient is remotely followed, the office-based visits can be limited to the initial postimplantation period and annual follow-ups, unless alerts or the patient’s health requires an urgent in-person check [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last decade the new generation of ICD devices that supports wireless technology has enabled remote monitoring of the device [ 3 - 6 ]. Consequently, in order to improve clinical practice of ICD follow-ups and to provide earlier detection of clinical problems, a wider use of remote patient monitoring (RPM) has been recommended by scientific associations in both Europe [ 5 ] and the United States [ 7 ], and has become the new standard of care for patient follow-up [ 8 - 10 ]. When a patient is remotely followed, the office-based visits can be limited to the initial postimplantation period and annual follow-ups, unless alerts or the patient’s health requires an urgent in-person check [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of remote monitoring in CRT and other cardiac implantable electronic devices (CIED) – implantable cardioverter-defibrillators (ICD) and pacemakers (PM) has been pointed out in numerous papers 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 . It has positive impact on patients’ quality of life, healthcare costs reduction and, what is the most important, clinical outcome of HF patients 5 , 6 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Revisiting in the future such a telephone based approach to remote monitoring would require a substantial implementation of novel technologies. It is also of great importance for the CIED clinic to have a structured pathway to react to alarms or events detected via RM, as this may influence patient outcomes [19,20]. In a recently published analysis of the results of the Optimization of Heart Failure Management Using OptiVol™ Fluid Status Monitoring and CareLink™ (OptiLink HF) study, for example, RM appropriate reactions to intrathoracic fluid index threshold crossings alerts were associated with significantly improved clinical outcomes in patients with advanced HF.…”
Section: Early Detection Of Atrial Arrhythmias: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…Reduced ejection fraction [12,13], chronic renal failure [14], arrhythmogenic right ventricular cardiomyopathy [15,16], Brugada syndrome [17,18] and dilated-hypertrophic cardiomyopathy [11] have been reported as risk factors for critical events. Other studies demonstrated that RM may improve outcomes in patients with severe heart failure and atrial fibrillation [19,20]. An analysis of the FOLLOWPACE study [21] evaluated different patient-and procedure-related characteristics to identify subjects at high risk of complication following pacemaker implantation.…”
mentioning
confidence: 99%